2015
DOI: 10.1155/2015/830618
|View full text |Cite
|
Sign up to set email alerts
|

A High-Density SNP and SSR Consensus Map Reveals Segregation Distortion Regions in Wheat

Abstract: Segregation distortion is a widespread phenomenon in plant and animal genomes and significantly affects linkage map construction and identification of quantitative trait loci (QTLs). To study segregation distortion in wheat, a high-density consensus map was constructed using single nucleotide polymorphism (SNP) and simple sequence repeat (SSR) markers by merging two genetic maps developed from two recombinant-inbred line (RIL) populations, Ning7840 × Clark and Heyne × Lakin. Chromosome regions with obvious seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 43 publications
7
28
1
Order By: Relevance
“…Another possibility is that a transcription factor controls both traits or induces a factor for recombination in this region. Segregation distortion can also arise because of conscious or unconscious selection by researchers during the mapping of populations (Li et al, 2015). Further analysis is required to clarify the cause of the skewed segregation in our study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Another possibility is that a transcription factor controls both traits or induces a factor for recombination in this region. Segregation distortion can also arise because of conscious or unconscious selection by researchers during the mapping of populations (Li et al, 2015). Further analysis is required to clarify the cause of the skewed segregation in our study.…”
Section: Discussionmentioning
confidence: 91%
“…The reason for the skewed segregation in our study is unclear. Segregation distortion is a common phenomenon in many plants and is recognized as a potentially powerful evolutionary force (Li et al, 2010;Li et al, 2015); however, its underlying mechanism is not understood (Cai et al, 2015). Suggested causes include aneuploidy, chromosomal translocation, competition among gametes, and the inheritance of alleles affecting the viability of the zygote, embryo, or seedling (Lashermes et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…SD is likely to represent one result of genetic incompatibilities between parental genomes that have been separated by reproductive barriers [48]. In this view, it is not surprising to find the level of SD to increase, both in the number of SD regions (SDRs) within a chromosomal set, and in the number of markers within each SDR, in intraspecific cross progeny involving genetically and geographically more distant parents [49]. In contrast to the latter work, which was carried out on wheat, a recent study on F 2 populations generated from several Arabidopsis thaliana accessions showed little correlation between the degree of genetic differentiation between the parental accessions and the probability of observing allelic distortion in their progeny [50].…”
Section: An Intriguing Issue In Wheat-alien Gene Transfer: Segregatiomentioning
confidence: 99%
“…This strategy ensures the accuracy and a high coverage of the final map. Similar strategies were successfully used for linkage mapping in different species, e g., of olive (Khadari et al 2010), globe artichoke and cardoon (Martin et al 2013), lentil (Verma et al 2015), poplar (Zhou et al 2015), and wheat (Li et al 2015).…”
Section: Mf Guindon Et Almentioning
confidence: 99%